2014
DOI: 10.1124/mol.113.089714
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin1 and Distinct CXCR4 Structures Are Required for Stromal Derived Factor-1 to Downregulate CXCR4 Cell-Surface Levels in Neuroblastoma

Abstract: CXC chemokine receptor 4 (CXCR4) is a G protein-coupled receptor (GPCR) located on the cell surface that signals upon binding the chemokine stromal derived factor-1 (SDF-1; also called CXCL 12). CXCR4 promotes neuroblastoma proliferation and chemotaxis. CXCR4 expression negatively correlates with prognosis and drives neuroblastoma growth and metastasis in mouse models. All functions of CXCR4 require its expression on the cell surface, yet the molecular mechanisms that regulate CXCR4 cell-surface levels in neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…Moreover, GATA2 knockdown experiences on human HSC suggest that expression of some GPCRs as well as the regulatory elements of their function can be directly perturbed under conditions of GATA2 insufficiency [50]. Strikingly, reduced GATA2 function leads to a decreased expression of filamin A and b-arrestin-1 [50], 2 proteins notably regulating CXCR4 cell surface expression and endocytosis and the chemotactic response of cells to CXCL12 [51][52][53], the anomalies of which might account for the downregulation of CXCR4 at the cell surface. If a reduced function for CXCR4 is also present in NK precursors, such an anomaly is anticipated to reduce their interaction with BM stromal [54] cells and to shorten their retention time in this compartment [15,18,19], as suggested in wild-type and humanized mice, thus possibly impinging on the differentiation program of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GATA2 knockdown experiences on human HSC suggest that expression of some GPCRs as well as the regulatory elements of their function can be directly perturbed under conditions of GATA2 insufficiency [50]. Strikingly, reduced GATA2 function leads to a decreased expression of filamin A and b-arrestin-1 [50], 2 proteins notably regulating CXCR4 cell surface expression and endocytosis and the chemotactic response of cells to CXCL12 [51][52][53], the anomalies of which might account for the downregulation of CXCR4 at the cell surface. If a reduced function for CXCR4 is also present in NK precursors, such an anomaly is anticipated to reduce their interaction with BM stromal [54] cells and to shorten their retention time in this compartment [15,18,19], as suggested in wild-type and humanized mice, thus possibly impinging on the differentiation program of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Data represent three or more independent experiments. IL-6 ELISA, membrane preparations, immunoprecipitations, Western blots (39), flow cytometry (40), and statistical analyses] are in SI Materials and Methods. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Greater expression of CXCR4 in NBs was correlated with high-stage disease and worse clinical outcome than lower expression of CXCR4 (43,44). Functional studies have demonstrated that inhibition of CXCR4 was an efficient strategy to inhibit NB cell proliferation and metastasis (45)(46)(47). A previous study by Ding et al demonstrated the inhibitory role of vandetanib on NB cell migration and invasion through downregulation of CXCR4 and MMP-14 expression (28).…”
Section: Discussionmentioning
confidence: 99%